First experience of laparoscopic colon resection with primary anastomosis for combat-related thoracoabdominal trauma with through-and-through colon injury - Iu. O. Mikheiev; K. V. Gumeniuk; Ya. V. Tielushko; D. S. Mialkovskyi; S. I. Savchenko (Сучасні медичні технології)
Aim: to demonstrate the possibilities and advantages of laparoscopic surgery in combat-related abdominal penetrating trauma with colon injury.